Sustainability Committees and Environmental Initiatives: Insights from Dual Banking Systems in Emerging Markets - Yunice Karina Tumewang; Rumaizah Azizah Al Adawiyah; Kemala Putri Ayunda (Journal of Islamic Monetary Economics and Finance, 2026)
Recently, companies have become more concerned with environmental sustainability, and many of them have established sustainability committees (SCs) to entrench sustainability in their strategic planning and corporate culture. Drawing upon insights from stakeholder and legitimacy theories, this study investigates the nexus between SCs and environmental initiatives (EI) in emerging markets having both conventional and Islamic banks.  Applying panel regressions, we find evidence indicates that the presence of an SC is positively associated with overall environmental scores, environmental products, environmental innovations, and resource reduction. Subsample analyses reveal that, for IBs, establishing SCs significantly affects overall environmental and resource reduction scores, suggesting that SCs in IBs may primarily drive symbolic (e.g., overall environmental and resource reduction scores) rather than substantive environmental efforts (e.g., environmentally-friendly products and innovations).  In contrast, SC establishment shows a significant effect across all four dimensions of EI for conventional banks (CBs), underscoring its more comprehensive role in shaping environmental outcomes within CBs. These findings have important theoretical, practical, and policy implications for bank managers, regulators, and other key stakeholders.